Analisis Perbedaan Abnormal Return Sebelum dan Sesudah Pemilihan Presiden Tahun 2019 pada Saham LQ45 yang Terdaftar di Bursa Efek Indonesia - Erwin Febriansyah; Furqonti Ranidiah; Umi Mustika (Jurnal Pasar Modal dan Bisnis, 2021)
Purpose – the purpose of this study is to out the difference in abnormal returns before and after the 2019 presidential election on LQ45 stock listed on the the Indonesia stock Exchange. Methods – this study uses event studies, observing the average abnormal returns for 10 days before the event date , and 10 days after the 2019 presidential election. Data used in this study include the stock price, daily closing, stock index. Return expectations using a market-adjusted model. The sample used is stocks that are included in the LQ-45 list on the Indonesia Stock Exchange. The data analysis technique used to answer the research hypothesis is a paired sample t-test. Finding – the finding in this study are Based on the analysis of paired samples t-test test results show that there is no significant difference in abnormal returns before and after the presidential election event. This is evidenced from the results of paired sample t test testing with a significance level of 0.589 greater than the level of significance that has been set at 0.05.